1999
DOI: 10.1007/s002329900487
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hemoglobin A and S on the Volume- and pH-Dependence of K-Cl Cotransport in Human Erythrocyte Ghosts

Abstract: K-Cl cotransport is abnormally active in erythrocytes containing positively charged hemoglobins such as Hb S (SS: beta6 Glu --> Val) or Hb C (CC: beta6 Glu --> Lys). The relatively younger age of erythrocytes in these diseases cannot completely account for the increased K-Cl cotransport activity. It has been suggested that these positively charged Hb may interact with the K-Cl cotransport system or one of its regulators and induce changes in its functional activity. We report here data on the volume- and pH-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…[21] Deoxygenation ) in sickle cells. [22] Luthra and Sears proposed that in β-thalassemia patients, oxidative damage induced by free globin chains has been implicated in the pathogenesis of the membrane abnormalities. He also mentioned that Na + , K + pump was reduced in thalassemialike cells, whereas it was increased in severe alpha-and betathalassemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Deoxygenation ) in sickle cells. [22] Luthra and Sears proposed that in β-thalassemia patients, oxidative damage induced by free globin chains has been implicated in the pathogenesis of the membrane abnormalities. He also mentioned that Na + , K + pump was reduced in thalassemialike cells, whereas it was increased in severe alpha-and betathalassemia cells.…”
Section: Discussionmentioning
confidence: 99%
“…2,28 Nevertheless, there is evidence that the presence of sickle hemoglobin (Hb S, ␤ 6glu3val ) or hemoglobin C (Hb C, ␤ 6glu3lys ) directly affects the activity and properties of KCC in RBCs and RBC ghosts. [29][30][31]7 demonstrated acid stimulation of KCC in SS RBCs and showed that acidification of SS RBCs produced an increase in cell density. 6,7 Bookchin et al 32 showed that SS reticulocytes were susceptible to acid-induced dehydration and suggested that most of the dense cells in sickle blood arose from a subpopulation of SS reticulocytes with high sensitivity to KCC-mediated dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…However, the volume-dependence of K-Cl cotransport on HbA and S in human erythrocyte ghosts suggests an alternative mechanism of participation of Hb in cell volume regulation [107]. K-Cl cotransport in white ghosts of human erythrocytes is volume-and pHindependent [107].…”
Section: Hb Oxygenation and Volume Regulationmentioning
confidence: 99%